2013
DOI: 10.1016/j.jvs.2012.09.034
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endograft type on inflammatory response after endovascular treatment of abdominal aortic aneurysm

Abstract: Objective: To evaluate the impact of endograft type on the inflammatory response after elective endovascular repair of abdominal aortic aneurysms. Methods: From January 2011 to November 2011, we included 100 consecutive patients who underwent elective abdominal aortic aneurysm endovascular repair. Thirteen patients were excluded from the analysis: four with cancer, three with autoimmune disease, two because of recent infection, two who were receiving long-term anti-inflammatory medication, and two because of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 22 publications
(36 reference statements)
6
74
0
2
Order By: Relevance
“…This finding is in accordance with the recent publication of Voûte et al 8 However, in the same report the authors showed that the implantation of stent grafts based on polyester was independently associated with a stronger inflammatory response. 8 Moulakakis et al, 9 observing a milder inflammatory activation in patients with a PTFE endograft, have confirmed this finding in a later report. In accordance with these reports it was found that the use of polyester endograft independently predicted PIS and was correlated with a greater than 10 times higher risk for an inflammatory response.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…This finding is in accordance with the recent publication of Voûte et al 8 However, in the same report the authors showed that the implantation of stent grafts based on polyester was independently associated with a stronger inflammatory response. 8 Moulakakis et al, 9 observing a milder inflammatory activation in patients with a PTFE endograft, have confirmed this finding in a later report. In accordance with these reports it was found that the use of polyester endograft independently predicted PIS and was correlated with a greater than 10 times higher risk for an inflammatory response.…”
Section: Discussionsupporting
confidence: 56%
“…In EVAR cases, the amount of contrast media, the endograft material, or the amount of mural thrombus within the aneurysm sac have all been implied as possible causative factors. 8,9,20,21 The type of anesthesia may also have a role by influencing the inflammatory cytokine response. 22 As most of the patients worldwide are operated on under general anesthesia, to avoid any possible bias all patients in this study were operated on under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations